AB1256 Development of a national service for biologic drug monitoring. (12th June 2018) - Perry, M.E.; ,
Abstract : Background: Monitoring serum levels of biological drugs has well recognised benefits for patients and health services. These include appropriate dosing, avoidance of overtreatment, identification of drug failure due to immunogenicity, cost and facilitation of switching therapy. 1 Objectives: To establish a national service for monitoring serum levels of biological drugs. Methods: National Services Scotland established a working group comprised of clinicians, lead pharmacist and Director of Public Health to help optimise biological drug prescribing. (Effective Prescribing Programme Biologics -EPPB). It was recognised that ad-hoc biologic drug monitoring (BM) posed a risk of variation in standards and inequity of access. Existing test volume and cost was established and a business case submitted to the CEO's of each Health Board in Scotland for a national service, testing adalimumab and infliximab twice yearly in 2265 patients. Potential cost savings based on drug withdrawl of 2.5%, 5%, 10%, and 15% in gastroenterology patients ranged from 400, 000Euro to 3.5 million Euro. Additional savings for dose reduction in rheumatology patients were not costed but likely to incur further financial advantage. Results: The case was accepted and service tendered. A single site in Glasgow will run the assays (purchased from Grifols) commencing December 2017. The cost modelling predicts a 50% reduction in cost per test compared to existing arrangements. Cost for the whole service will be divided between the commissioning Health Boards with outlay proportional to patient population. The EPPB developed specialty specific advice and an ordercomm with minimum dataset accessible from all Health Boards with the option of retrospective interrogation. A national educational event is scheduled to improve clinician confidence and awareness. Conclusions: To our knowledge this is the first national fully funded biologic drug monitoring service with access to all users of biological drugs. Its introduction will: 1. Support the implementation of national standards of care to ensure the effective and cost effective use of biologic medicines 2. Ensure equity of access to BM across Health Boards. 3. Provide a stronger position for procurement of biologic drugs (uncomplicated by additional service offerings) 4. Provide a sustainable service for Scotland, independent of the drug manufacturer. Reference: [1] Jani, et al. Clinical Utility of Random Anti-Tumor Necrosis Factor Drug Level Testing and Measurement of Antidrug Antibodies on the Long-Term Treatment Response in Rheumatoid Arthritis. Arthritis and Rheumatology 67:8;(2015) p2011–2019. Disclosure of Interest: None declared